A method of numerical simulation of flow separation at the inlet of a circular thin-walled pipe - Logachev, K.I.; Averkova, O.A.; Logachev, A.K.; Tolmacheva, E.I.; Gorlov, A.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2016)
A mathematical simulation method, a computational algorithm and a software program are developed to calculate a separated flow at the inlet of a circular thin-walled pipe in the case of a high-speed or low-speed incident flow. In order to construct a discrete model, the stationary discrete vortex rings are used. The adequacy of the proposed method is confirmed by the satisfactory qualitative and quantitative agreement with the numerical results obtained by other authors.